Limiting Irrigation Water Quality Indices of several rivers, wells and springs in Dohuk governorate - Akram Othman Esmail; Vahil Ismael Barwari; Omar Anwar Rekani (Zanco Journal of Pure and Applied Sciences, 2022)
The investigation was done during 2018, that included the chemical analysis of 30 water samples which were taken from 10 wells,10 springs and 10 rivers in Dohuk. The results showed that 10 , 26.67 , 53.33 and 10% of tested water samples had excellent ,good, average and poor quality relying on quality index for irrigation water and Brazilian classification(2012) that located between zero to 13.34.On the other hand depending on Meireles et al., classification (40 ,40 ,16.67 and 3.33) percentage of the studied water resources recorded medium , high ,severe and low restriction of applying for irrigation uses respectively with the quality index for irrigation of ( 37.38 to 42.02). The results showed the difference between the results of two applied systems for irrigation water category.